Efficacy, chemical composition, and pharmacological effects of herbal drugs derived from Fritillaria cirrhosa D. Don and Fritillaria thunbergii Miq. - Wu, Fan; Tian, Mei; Sun, Yuefeng; Wu, Changhao; Liu, Xue (Frontiers in Pharmacology, 2022)
Fritillaria cirrhosa D. Don and F. thunbergii Miq. are plants with special characteristics that belong to the genus Fritillaria in family Liliaceae. They are used in traditional Chinese medicines and administered extensively in clinical practice and have notable medicinal value in treating cough, bronchitis, pneumonia, lung injury, cancer, and other diseases. In this review, the history, origin, similarities, and differences in efficacy, chemical composition, and pharmacological outcomes of FRC and FRT (i.e., the drugs obtained from F. cirrhosa and F. thunbergii, respectively) have been analysed. This study lists various valuable pharmacological effects of FRC and FRT, including antitussive, expectorant, anti-inflammatory, anti-oxidant, and anticancer effects. Thus, it offers a basis for the medical application and further research into the pharmacological impacts of these two drugs. Consequently, new drugs with specific therapeutic effects are expected to be developed. As F. cirrhosa is gradually becoming a rare and expensive herb, the possibility of FRT replacing FRC must be studied by comparing the places of origin, efficacy, chemical composition, and pharmacological properties of the two herbs.